2017
DOI: 10.2174/1874325001711011001
|View full text |Cite
|
Sign up to set email alerts
|

Controversies in the Management of the First Time Shoulder Dislocation

Abstract: Background:Traditionally, initial management of first anterior shoulder dislocations consists of reduction of the glenohumeral joint followed by a period of immobilization and subsequent physical therapy to recover shoulder range of motion and strength. This traditional approach in management is now controversial due to the high rate of recurrence. The aim of this paper is to review and discuss the literature about the global management of patients presenting with first-time traumatic anterior glenohumeral dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…However, several other orthopedic trials have demonstrated that despite rehabilitation being the safe option, it may not always be the best option. Specifically, patients with acute first‐time shoulder dislocations were historically treated nonoperatively [2]. Nevertheless, in recent years we have been seeing a shift in the management of these patients towards early arthroscopic stabilization largely due to the publication of high‐level evidence supporting early surgical intervention [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, several other orthopedic trials have demonstrated that despite rehabilitation being the safe option, it may not always be the best option. Specifically, patients with acute first‐time shoulder dislocations were historically treated nonoperatively [2]. Nevertheless, in recent years we have been seeing a shift in the management of these patients towards early arthroscopic stabilization largely due to the publication of high‐level evidence supporting early surgical intervention [18].…”
Section: Discussionmentioning
confidence: 99%
“…A common approach to the care of a patient after a glenohumeral joint dislocation is to place the patient's shoulder in a sling for comfort, with permitted pain-free isometric exercise along with passive and assisted elevation up to 100°. 16 This is followed by a nonaggressive rehabilitation protocol for 2 months until full recovery, which includes progressive range of motion, strength, proprioception, and return to functional activities. 16 More aggressive return-to-play protocols with accelerated timelines and functional progression have been studied, including in a multicenter observational study that followed 45 contact intercollegiate athletes prospectively after in-season anterior glenohumeral instability.…”
Section: An Increasing Number Of Dislocations Portends a Poor Outcome With Nonoperative Treatmentmentioning
confidence: 99%
“…16 This is followed by a nonaggressive rehabilitation protocol for 2 months until full recovery, which includes progressive range of motion, strength, proprioception, and return to functional activities. 16 More aggressive return-to-play protocols with accelerated timelines and functional progression have been studied, including in a multicenter observational study that followed 45 contact intercollegiate athletes prospectively after in-season anterior glenohumeral instability. Thirty-three of 45 (73%) athletes returned to sport for either all or part of the season after a median 5 days lost from competition, with 12 athletes (27%) successfully completing the season without recurrence.…”
Section: An Increasing Number Of Dislocations Portends a Poor Outcome With Nonoperative Treatmentmentioning
confidence: 99%
“…3,[38][39][40] In younger patients, rates of recurrence as high as 92-96% have been reported. 6 An incidence study of shoulder instability among athletes at a US military academy showed that 85% experienced a recurrent event within a 9-month period. 7 A systematic review showed that there were some limited data to support primary surgery following a first-time TASD in young adults engaged in demanding physical activities (i.e.…”
Section: Prediction Model: Non-surgical Cohortmentioning
confidence: 99%